Backtalk: Keep religion out of mindfulness. (December 2019) - Armstrong, Thomas
Mindfulness practices have become increasingly common in the United States and elsewhere in the world. The fact that mindfulness originally emerged out of Buddhism raises questions about whether public school teachers using it in their classrooms are violating the separation of church and state. Thomas Armstrong argues that contemporary mindfulness rests on a solid foundation of scientific research and can help students improve their self-regulation, executive functioning, sustained attention, and other school-worthy skills. There is a danger, however, that injecting Buddhist or Hindu-associated gestures, postures, words, or concepts into the teaching may violate the First Amendment. Public school teachers are enjoined to be scrupulously vigilant in presenting mindfulness practices in a totally secular way .